The Metabolic Pattern of Idiopathic REM Sleep Behavior Disorder Reflects Early-Stage Parkinson Disease - Meles, Sanne K.; Renken, Remco J.; Janzen, Annette; Vadasz, David; Pagani, Marco; Arnaldi, Dario; Morbelli, Silvia; Nobili, Flavio; Mayer, Geert; Leenders, Klaus L.; Oertel, Wolfgang H. (Journal of Nuclear Medicine, 2018)
Idiopathic REM sleep behavior disorder (iRBD) is considered a prodromal stage of Parkinson disease (PD) and other Lewy body disorders. Spatial covariance analysis of F-FDG PET data has disclosed a specific brain pattern of altered glucose metabolism in PD. In this study, we identify the metabolic pattern underlying iRBD and compare it with the known PD pattern. To understand the relevance of the iRBD pattern to disease progression, we studied the expression of the iRBD pattern in de novo PD patients. The iRBD-related pattern was identified in F-FDG PET scans of 21 patients with polysomnographically confirmed iRBD and 19 controls using spatial covariance analysis. Expression of the iRBD-related pattern was subsequently computed in F-FDG PET scans of 44 controls and 38 de novo, treatment-naïve PD patients. Of these 38 PD patients, 24 had probable REM sleep behavior disorder (RBD) according to the Mayo Sleep Questionnaire. Neuropsychologic evaluation showed mild cognitive impairment in 20 PD patients (PD-MCI), of whom 16 also had concomitant RBD and roughly half (11/20) had bilateral motor symptoms. The iRBD-related pattern was characterized by relative hypermetabolism in the cerebellum, brain stem, thalamus, sensorimotor cortex, and hippocampus, and by relative hypometabolism in the middle cingulate, temporal, occipital, and parietal cortices. This topography partially overlapped with the PD-related pattern (PDRP). The iRBD-related pattern was significantly expressed in PD patients compared with controls ( < 0.0001). iRBD-related pattern expression was not significantly different between PD patients with and without probable RBD, or between PD patients with unilateral or bilateral parkinsonism. iRBD-related pattern (iRBDRP) expression was higher in PD-MCI patients than in PD patients with preserved cognition ( = 0.001). Subject scores on the iRBD-related pattern were highly correlated to subject scores on the PDRP ( = 0.94, < 0.0001). Our results show that the iRBDRP is an early manifestation of the PDRP. Expression of both PDRP and iRBDRP was higher in patients with a more severe form of PD (PD-MCI), which indicates that expression of the 2 patterns increases with disease severity.